ALGORITHM FOR GROUND VEHICLE STABILIZER OPTIMAL SYNTHESIS - Sushchenko, Olga A.; Kvasha, Sergey O.; Kharatin, Ivan M. (Proceedings of National Aviation University, 2009)
Approaches to creation of the ground vehicle stabilizer optimal synthesis are considered. Features of the computational procedure of the optimal synthesis for the studied system are defined. Simulation results are represented.